(untitled) (Journal of the College of Basic Education, 2023)
To overcome the development of drug resistance, it is necessary to find a new class of antimicrobial compounds possessing different mechanism or chemical properties from those that are used commonly for the treatment of the diseases which are caused by Candida albicans. This study was designed to investigate the antifungal activity of Diacetyl against Candida albicans isolates with a total of forty eight Candida albicans isolates which was isolated from sputum, vagina and urine sample of different patients were tested against several concentrations of Diacetyl compound (30,60,120,180)µg/ml and for different incubation time to examine the inhibitory activity of the compound in vitro. All urine isolates showed 100% complete inhibition to(30,60,120,180) µg/ml concentrations after 24,48,72 hrs incubation at 37C°,while only three vaginal isolates 30% and eleven sputum isolates 42.3% showed resistance after 48 hrs incubation to 30 and 60 µg/ml concentrations. It seems that Diacetyl compound has a potent antifungal activity against Candida albicans in vitro.